Influence of different opacities and layering technique of nanotechnology composite resins regarding the wavelength and fluorescence intensity: in vitro study - Carla Portocarrero-Flores; Thais Alcandré; Alberth Correa-Medina (Universidad de Concepción., 2024)
Objective: To evaluate the influence of opacity and the layering technique on the fluorescence of different composite resins. Materials and Methods: Two opacities (enamel and dentin) and the layering technique (enamel + dentin) of the composite resins: Filtek® Z350 and Palfique LX5 were evaluated in vitro. Composite resin discs were fabricated using a preformed matrix of 10 mm diameter and 0.5 mm thick for the single opacity groups and 10 mm thick for the layering technique groups, using 2 layers of 0.5 mm thickness of each opacity (n = 5). Specimens were analyzed using the Raman spectroscopy method. Data were analyzed using the Kruskall-wallis and Mann-Whitney U tests. Results: When evaluating the intensity of fluorescence, no statistically significant difference was found when comparing the layering technique and enamel opacity (p2> 0.05) and an increase in the dentin opacity value for both brands of composite resin. Regarding wavelength, no statistically significant difference was found when comparing the layering technique with enamel opacity and dentin opacity for both Filtek® Z350 and Palfique LX5® composite resins (p2 > 0.05). Conclusions: The fluorescence intensity of the layering technique is similar to enamel opacity for both composite resins. Likewise, the wavelength of the layering technique is similar to the enamel opacity and dentin opacity for both brands.